Composting of sawdust and fertilization of pumpkin culture in the South of the state of Roraima (Research, Society and Development, 2020)
The south of the state of Roraima is a region where there is a predominance of small farmers, most of whom are without capital. The use of organic compounds is an alternative to reduce costs through nutrient cycling. The use of organic waste available in the region, mainly sawdust from sawmills, can be an alternative for the production of compounds. Given this, the objective was to produce organic compounds using sawdust (SD) and sheep manure (EM) in different proportions and to evaluate the production of pumpkin culture when fertilized with the compounds in a sandy soil. The work was developed in two stages: the first the production of organic compounds and the second the evaluation of the production of the pumpkin culture. Two compounds were produced with different proportions of SD and EM. To evaluate the production of pumpkin culture, the following treatments were used: 1. cultivation without fertilization (control); 2. compound 1 (C1) (50% SD + 50% EM); 3. compound 2 (C2) (75% SD + 25% EM); 4. EM; 5. biofertilizer (Bio) and 6. mineral fertilization (N-P-K). It was observed that C1 started and ended with a lower C/N ratio than C2. The temperature (ºC), humidity and pH differ little between the compounds. Regarding the productivity of the pumpkin culture, the treatments EM, C1 and C2 were the ones that produced the most, however, C1 and C2 did not differ from mineral fertilization. It was concluded, therefore, that organic compounds can be used to replace mineral fertilizer.